Fatigue behaviour of cold sprayed metals and alloys: critical review. (1st September 2016) - Cavaliere, P.; Silvello, A.
Abstract : Cold spray is an innovative coating technology mainly based on the high speed impact of metallic particles on various substrates. Low temperature carrier gases (air, He and N2 ) accelerate particles (usually 1–50 μm in diameter) to high velocity (typically 300–1200 m s − 1 ) that is generated through a convergent–divergent de Laval type nozzle. Particles' severe plastic deformation occurs at temperature well below the melting point leading to the unique mechanical properties experienced by cold spray coatings. In the recent past, different papers were published describing the fatigue properties of cold sprayed metals and alloys. Generally, mechanical results are related to the microstructural evolution due to different coating materials and different processing parameters. The present paper presents a critical review of the results belonging to the available literature on fatigue properties of cold sprayed coatings.